Protective Effects of Lemna minor Linn. On Hepatic and Cognitive Impairments in Acetaminophen Induced Hepatic Encephalopathy in Rats - C H, Chandini; Sarkar, Mayukh; D R, Nishanth; K R, Roopesh; G, Karthik; Kumar, Mahesh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aim: Lemna minor Linn., an aquatic plant, is a promising novel therapeutic agent that has been traditionally used in ethnobotanical practices as an ecofriendly supplement for the management of various ailments. This study involves the evaluation of ethanolic extract of Lemna minor Linn. against Paracetamol-induced Hepatic Encephalopathy using in vitro and in vivo Models. Methods: The acute oral toxicity study of the ethanolic extract of Lemna minor (EELM) was conducted following the OECD-425 guidelines over a 14-day period. A total of nine animals were used for this toxicity assessment. The EELM was tested in Paracetamol(PCM)-induced bioactivation animal model at two different dosages 200 and in comparison with silymarin as a standard compound. The In vivo experimental study was conducted using Sprague Dawley rats which was divided into 5 groups each group containing 6 animals so the total no of animals used in the study was 30 animals. The treatment groups included: normal control ( ), 100mg/kg silymarin (standard) and the EELM of two different doses of 200 and , p.o were administered to rats 10 hr before paracetamol ( ) treatment. Rats were orally administered their respective doses every day for total 30days. Paracetamol-induced oxidative liver damage disrupted normal levels of liver enzymes, total protein, and bilirubin, while also depleting antioxidant reserves. This oxidative stress was strongly associated with paracetamol toxicity, leading to a marked depletion of glutathione (GSH) and impairing both memory and cognitive function in the animals. Behavioral parameters are performed to evaluate the effect of drugs on cognitive behaviour of animals. Morris water maze test was performed to study how animals learn and remembers the spatial information relying on distal cues to locate the hidden platform in an opaque water. Additionally, elevated plus maze was performed to measures the anxious behaviour of rats, the criterion was tested based on the conflict between rats innate instincts to explore new environment and avoid open, well-lit areas. The potential protective effects of EELM was evaluated by measuring serum enzyme levels and antioxidants status in the liver and brain, further histopathological analysis was performed respectively. Results: The acute toxicity study did not report any mortality or toxicity signs in animals. PCM toxicity led to a statistically increase in the liver and body weight, along with brain water content. The PCM-intoxicated group exhibited a marked reduction in the level of superoxide dismutase (SOD) and glutathione (GSH) in the brain and liver, as well as an increase in lipid peroxidation and serum biomarkers (AST, ALT, ALP, and total bilirubin). EELM significantly ( ) reduced liver injury by inhibiting ALT, AST and ALP levels in serum. SOD, GSH and MDA liver content were significantly ( ) elevated by EELM, compared to PCM treated rats. Comparing the treatment and induced group, the treated group successfully recovered the activity of antioxidant levels and also been acknowledged for restored liver functioning by alleviating oxidative stress and also GSH level in brain was significantly increased by EELM and preserved the histology of brain, which was chronically produced over a period of 30 days. Conclusion: The findings of this investigation indicate the traditional use of Lemna minor in hepatoprotection and neuroprotection by regulating oxidative stress and mitigating reactive oxygen species (ROS). The insights gained from this research contribute to the development of novel therapeutic agents and paves the way for further studies on Lemna minor to enhance health outcomes, particularly in the management of neurodegenerative diseases.